2007
DOI: 10.1080/10428190701534408
|View full text |Cite
|
Sign up to set email alerts
|

Detection of simian virus 40 DNA sequences in Egyptian patients with different hematological malignancies

Abstract: SV40 DNA sequences have been detected in non-Hodgkin's lymphoma patients. A link between SV40 and NHL is biologically plausible since SV40 causes hematological malignancies in laboratory rodents. We investigated 266 Egyptian cases of hematological malignancies (158 NHL, 54 HD, 26 ALL, 13 AML, 8 CLL, 7 CML) and 34 subjects as a control for detection of SV40 DNA using nested PCR. SV40 DNA sequences were found in (53.8%) of NHL, (29.6%) of HD and in (40.7%) of different types of leukemia cases. Frequency of SV40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…SV40 DNA sequences have been detected in B-lymphocytes from healthy blood donors and immunosuppressed patients (David et al, 2001;Dolei et al, 2000;Martini et al, 1996). B-cell lymphomas arise in some hamsters inoculated with SV40 (Cicala et al, 1992;Diamandopoulos, 1973;Matthews et al, 1987) and human B-cell lymphomas were found in recent investigations to contain SV40 markers (Amara et al, 2007;David et al, 2001;Meneses et al, 2005;Nakatsuka et al, 2003;Shivapurkar et al, 2002;Vilchez et al, 2002b;Zekri et al, 2007). Our findings here suggest that B-cell-rich tonsil tissue might play a role in viral persistence.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…SV40 DNA sequences have been detected in B-lymphocytes from healthy blood donors and immunosuppressed patients (David et al, 2001;Dolei et al, 2000;Martini et al, 1996). B-cell lymphomas arise in some hamsters inoculated with SV40 (Cicala et al, 1992;Diamandopoulos, 1973;Matthews et al, 1987) and human B-cell lymphomas were found in recent investigations to contain SV40 markers (Amara et al, 2007;David et al, 2001;Meneses et al, 2005;Nakatsuka et al, 2003;Shivapurkar et al, 2002;Vilchez et al, 2002b;Zekri et al, 2007). Our findings here suggest that B-cell-rich tonsil tissue might play a role in viral persistence.…”
Section: Discussionsupporting
confidence: 61%
“…The nature of interaction of SV40 with lymphoid tissue is unclear. Bcell lymphomas occur in small-animal models of SV40 infection (Cicala et al, 1992;Diamandopoulos, 1973;Matthews et al, 1987), and SV40 is associated with some B-cell lymphomas in humans (Amara et al, 2007;David et al, 2001;Meneses et al, 2005;Shivapurkar et al, 2002;Vilchez et al, 2002b;Zekri et al, 2007). Therefore, B-cell-rich tissues such as tonsils may represent a site that harbors SV40.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a study conducted with an innovative analysis, known as RNA sequencing (RNA-seq), identified SV40 mRNAs, in tumor samples from low-grade glioma affected patients (219). Different lympho-proliferative disorders (85, 239, 254, 255), including non-Hodgkin's lymphoma (79, 247251, 260) have also been associated with SV40 infection. It has been reported that the homologous and autologous implantation of SV40-transformed cells in humans caused the growth of nodules, thus suggesting that this PyV presents oncogenic capacity in humans (261).…”
Section: Association Of Sv40 With Human Tumorsmentioning
confidence: 99%
“…Moreover, few polymerase chain reaction (PCR) studies have shown the presence of SV40 in lymphomas with contradicting results. Two Egyptian studies using multiplex nested PCR have shown that SV40 DNA sequences were found in 53.8% of NHL patients in both series [ 23 , 24 ]. Other studies found 13, 10, 14, 42, and 43% incidence of SV40 in NHL, respectively [ 17 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%